Evaluasi Usability Pada Aplikasi KRL Access Dengan Menggunakan Metode Evaluasi Heuristik - Venzy Pertiwi; Ismiarta Aknuranda; Satrio Hadi Wijaya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
KRL Acess is the official mobile application owned by PT Kereta Commuter Indonesia that can be used by Jabodetabek KRL users to find for the information about train arrival schedules and routes. Users of the KRL Access application certainly have a number of problems when using the application, both positive and negative issues. In order to achieve the KRL Acess's purpose, ussability sistem can allow the users to get the results as expected. This research was conducted by using heuristic evaluation method to find out the usability problem that might occured in KRL Access. The evaluators that involved in this heuristic evaluation process were 4 evaluators of ussability expert. Usability evaluation with the heuristic evaluation method resulted in finding usability problems with total amount of 24 problems were founded by usability expert evaluator. From the total amount of 24 usability problems, it was found that the average severity rating that could be classified into 3 of 4 categories namely catastrophic, mayor, dan minor. The highest average severity rating is owned by the H-3 (User control and freedom) and H-10 (Help and documentation) principles. Each heuristic principle has an average severity rating of 2.75. While the most usability problems are found in the H-1 heuristic principle (Visibility of system status) with 28.12% of the overall usability problems.